Cognitive model construction and assessment of data analysis ability based on CDA - Wu, Xiaopeng; Zhang, Yi; Wu, Rongxiu; Tang, Xiuxiu; Xu, Tianshu (Frontiers in Psychology, 2022)
This study used cognitive diagnostic assessment (CDA) as the basic theory framework. First, five experts were recruited to construct the cognitive model of data analysis ability for junior high school students, which was used to build the ideal assessment model. Q-matrix was then constructed based on the ideal assessment model. Second, the assessment tool was designed based on the Q-matrix and its reliability was evaluated. Last, the data of 503 Chinese 9-th grade students were analyzed and the results suggested that the probability of mastering the attributed of interpretation and inference of data is relatively low, only 60% or so; the probabilities of the rest of attributes were evenly distributed with about 70%. According to the results, we explored the learning path and learning progression of students’ data analysis abilities, and three students with the same total score was analyzed and the personalized diagnosis information was obtained.